IMPLEMENTASI MULTI-AGENT UNTUK OTOMATISASI KONTEN PROMOSI DIGITAL PADA UMKM - Andini Hidayatun Nihmah (Universitas Lampung, 2026)
Micro, Small, and Medium Enterprises (MSME) often face challenges in producing engaging and consistent digital promotional content due to limited time, resources, and creative capabilities. This study aims to develop a CrewAI-based content creator assistant system to automate promotional content creation. The system was developed using Research and Development (R&D) methods with a Multi-Agent System approach consisting of a Content Planning Agent, a Caption Generator Agent, and a Visual Recommendation Agent. Implementation was carried out using Python on Google Collaboratory, utilizing the Large Language Model (LLM), the OpenAI API, and the BLIP model for product image analysis. Evaluation of 17 MSMEs was carried out based on time efficiency, ease of use, and user satisfaction. The results showed that the system was able to reduce the average content creation time from 52.65 minutes to 6.71 minutes, with an efficiency of 87.26%. In addition, the system obtained an ease of use score of 3.36 and a user satisfaction score of 3.28 on a 4-point Likert scale. These results indicate that the CrewAI-based multi-agent approach is effective in helping MSMEs produce promotional content more quickly and easily